Análise do turismo em Aquiraz - Ceará: política, desenvolvimento e sustentabilidade - Sousa, Michele (2005)
The present work has for main objective to verify the problems in the cultural scopes, ambient and socioeconomics, analyzing the influence of the tourist activity in the constitution and aggravation of these processes in the City of Aquiraz - CE. For this, the following specific objectives had been analyzed: to carry through historical boarding of the City and shortened socioeconomics picture; to show to the evolution of the public politics of tourism and its importance while line of direction for the development of the tourist activity, verifying the existence and repercussion of these in Aquiraz; to identify the social, ambient and economic impacts in the littoral communities, inquiring its Inter-relations with the tourist activity and to search the socioeconomics development of the City of Aquiraz, in the space-time of 10 years (1995 - 2004), taking for base the tourist activity for this development. The employed methodology consisted of descriptive analysis of the data, which had had primary and secondary origin. Also, the techniques of half-structuralized interview and application of questionnaires with the inhabitants of the communities, tourist had been used and people who work in the tourist activity. Aquiraz was chosen for the study of case focused in this work for being one of the most visited localities of the Ceará, according to research of the Secretariat of Tourism of the State of Ceará - SETUR-CE. Being the tourism, however, an activity that use to come followed of social, economic and ambient redefinitions, mainly in the use of the time, the spaces and of the territories the research becomes excellent to evaluate the "contributions" that the tourism brings to the City. In this direction, the inquiry contributes for the exposition of the reality of the tourist activity in Aquiraz, being able to guide enterprising strategies in the field of the tourism, especially in the aquiraense coast, that comes being explored, through the “sun and sea" tourism, only.